A performative history of STEM crisis discourse: the co-constitution of crisis sensibility and systems analysis around 1970. Issue 3 (4th May 2021) - Zheng, Lei
ABSTRACT: The STEM crisis discourse enacts a crisis sensitivity that governs the way of thinking and feeling about change in relation to techno-science. This article examines how this crisis sensitivity is historically co-constituted with systems analysis to configure the global, the future, and the accountable subjects as the objects of techno-scientific control in the early postcolonial era. The analytical approaches are historical epistemology and performativity theory. The discussions rely on the archives and publications of international institutes (e.g. UNESCO, the Club of Rome, IIASA) that adopted systems analysis to diagnose the 'world crisis' in and beyond education around 1970. The article argues systems analysis enacted a techno-scientific vision and calculation that collapsed the global and the future into a state of crisis, self-referentially enunciated itself as the intellectual and moral solution, and differentially included particular subjects as latent threats to the whole world for preemptive control.